Factors contributing to the sustained implementation of an early childhood obesity prevention intervention: The INFANT Program - Love, Penelope; Laws, Rachel; Taki, Sarah; West, Madeline; Hesketh, Kylie D.; Campbell, Karen J. (Frontiers in Health Services, 2022)
Background The INFANT Program is an efficacious, group-based program for first-time parents, delivered at three-monthly intervals when INFANT are aged 3–18 months through an existing universal care service in Victoria, Australia. Many lessons have been learnt from its origins as a cluster randomized control trial to its small-scale, community-level implementation. This study aimed to describe factors contributing to its sustained implementation to inform large-scale implementation across Australia. Methods This study used a multi-site qualitative exploratory approach. INFANT facilitators trained between 2013 and 2017 were sent an online survey, with optional telephone interviews. The Consolidated Framework for Implementation Research (CFIR) was selected as the underpinning theoretical framework as it offered the opportunity to explore a breadth of possible barriers and enablers across patterns of implementation (never, discontinued, ongoing). Results All participants were female (n = 31), the majority were Maternal and Child Health Nurses (48%), representing five regional and nine metro local government areas (LGAs), across all patterns of implementation (never implemented n = 4; discontinued implementation n = 5; ongoing implementation n = 5). All consenting participants were interviewed (n = 11) representing four regional and seven metro LGAs, across all patterns of implementation (never implemented n = 3; discontinued implementation n = 4; ongoing implementation n = 4). The main reason for attending INFANT Program training was to become skilled to implement the program. Mapping identified barriers and enablers to the CFIR revealed the inner and outer settings and implementation process to be of greatest influence. Main differences between LGAs with ongoing and discontinued implementation related to funding availability, organizational management support and endorsement, organizational resourcing and capacity, integration into routine practice and establishing role clarity with partner organizations, and planning for sustained implementation from the start. Conclusion This study provides important insights into the barriers and enablers to the sustained implementation of an evidence-based intervention (the INFANT Program) during small scale community-level implementation. The authors therefore contend that the pre-requisite for scale-up of a population health intervention is not just proof of effectiveness but also proof of sustained implementation at the local/organizational level. Study findings have broad transferability given their similarity to those identified for health promotion interventions implemented globally, in healthcare, education and community settings.